Reimagining and redesigning a post-COVID sporting events: Mapping global sporting experiences - Sagar, M.; Kalort, N. (Co-creating the post COVID-19 world: Exploring sustainable paths, 2021)
The spread of Coronavirus has not only affected the countries and their economies at large but has also impacted a lot on the professional sports like IPL 2020. This chapter tries to study the role of media management in rediscovering, redesigning and reinventing the strategies to overcome this crisis in IPL 2020. To this end, the general effects of the pandemic on sports and the role of media managers will be briefly outlined, followed by a discussion of matches played behind closed doors. Based on the major sports events affected due to Pandemic COVID-19 sporting events of which some were held, and some being cancelled are being discussed in the perspective of how they manage the events during COVID-19 crisis through reportage and coverages. As a result, the stakeholder interest and professional sports bodies came up with solutions to maintain social distancing and bio bubble as a solidarity and certain measures of possible self-regulations.